2015
DOI: 10.5539/jas.v7n6p197
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel 2S Albumin with Antitryptic Activity from Caryocar brasiliense Seeds

Abstract: Proteinaceous and non-proteinaceous compounds with insecticidal activities have been isolated from plant sources. Here, protein extracts from Pequi seeds (Caryocar brasiliense) showed in vitro activity against trypsin-like enzymes. However, no activity was obtained against cancer cells, phytopathogenic fungi or human pathogenic bacteria. Further purification was performed by using trypsin-Sepharose affinity chromatography. Electrophoretic analysis revealed a single protein compound with molecular mass of appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, studies using extract, fractions, and isolated metabolites from C. ensiformis indicated their activity against M. incognita but did not present hemolytic activity (Rocha et al, 2017). Studies using protein extract of Caryocar brasiliense seeds demonstrated no hemolytic activity, despite its insecticidal potential against pest insects in in vitro tests (Costa, Franco, Migliolo, & Dias, 2015). Solanum capsicoides, a plant from the Solanaceae family, also showed no hemolytic effect (Petreanu et al, 2016).…”
Section: Bioassmentioning
confidence: 99%
“…On the other hand, studies using extract, fractions, and isolated metabolites from C. ensiformis indicated their activity against M. incognita but did not present hemolytic activity (Rocha et al, 2017). Studies using protein extract of Caryocar brasiliense seeds demonstrated no hemolytic activity, despite its insecticidal potential against pest insects in in vitro tests (Costa, Franco, Migliolo, & Dias, 2015). Solanum capsicoides, a plant from the Solanaceae family, also showed no hemolytic effect (Petreanu et al, 2016).…”
Section: Bioassmentioning
confidence: 99%
“…The 2S albumins generally have conserved set of cysteine residues which forms four disulfide bridges; two inter-chain bridges found between smaller and larger subunit; and other two intra-chain bridges present within the larger subunit [30,31]. Apart from this, 2S albumins performs plethora of functions such as antibacterial, antifungal and antitryptic and serine protease inhibitory activity as reported from different plant species [32][33][34][35]. The exact mechanism of the antifungal and antibacterial activity of 2S albumins is not well characterized.…”
Section: Introductionmentioning
confidence: 99%